Mechanisms of insecticide resistance in field populations of Aedes aegypti (L) from Quintana Roo, Southern Mexico - Flores Suárez, Adriana Elizabeth; Salomón Grajales, Jaime; Fernández Salas, Ildefonso; Ponce García, Gustavo; Lozano Fuentes, Saúl; Black, William C.; Brodgon, William (2006)
Potential insecticide-resistance mechanisms were studied with the use of biochemical assays in Aedes aegypti (L.) collected from 5 municipalities representing the north part of Quintana Roo: Benito Juarez, Cozumel, Isla Mujeres, Lazaro Cardenas, and Solidaridad. The activities of α and β esterases, mixed-function oxidases (MFO), glutathione-S-transferase (GST), acethylcholinesterase (AChE), and insensitive acethylcholinesterase (iAChE) were assayed in microplates. Three replicates were performed for each enzyme and 60 males and 60 females were analyzed in each population. The New Orleans (NO) susceptible strain of Ae. aegypti was used as a susceptible reference and the threshold criteria for each enzyme were the highest NO absorbance values. In none of the 6 tests were absorbance values correlated in males and females. α esterases were elevated in Benito Juarez, Cozumel females and in Lazaro Cardenas males and females. β esterases were elevated in Benito Juarez, Cozumel females and in Cozumel and Lazaro Cardenas males. Elevated esterases suggest potential insecticide-resistance mechanisms against organophosphate, carbamate, and some pyrethroid insecticides. Slightly elevated levels of MFOs appeared in Lazaro Cardenas females and in Cozumel, Isla Mujeres, and Solidaridad males. Mechanisms involving iAChE or GST were not apparent.